Public Support for the Accommodation of Religious Diversity: The Interplay Between Religious Identification, Threat Perception, and Cross-Group Friendships - Fierro C., Jaime (Journal for the scientific study of religion, 2025)
Accommodating new religious communities has become a central issue in Western Europe. However, the role of religious identification in shaping intergroup relations still needs to be better understood. This study addresses this gap by analyzing the factors influencing public support for the accommodation of religious diversity, drawing on two statistically representative surveys conducted in Catalonia, Spain. The results revealed that religious identification moderates the relationship between the perception that religions other than Catholicism threaten society's way of life and the level of support for accommodating religious diversity. Contrary to initial assumptions, practicing Catholics were more supportive of religious accommodation than nonpracticing Catholics and nonbelievers, regardless of the level of threat they perceived. Moreover, cross-group friendships mitigated the negative impact of perceived threat on support for religious accommodation, particularly among nonbelievers. Overall, the findings underscore the importance of cross-group friendships in fostering more inclusive societies and provide valuable insights for religious governance.